Implementation of Good Corporate Governance Principles in Village Fund Management in Jambanan Village Government, Sidoharjo, Sragen - Bella Rima Setiyawati; Widyarti, Maria Th Heni; Romangsi, I Nyoman (Indonesian Scientific Publication, 2025)
Village development in Indonesia is one of the main focuses of achieving overall community welfare. With Law No. 3 of 2024 on Village Development, the government emphasizes the importance of effectively and efficiently managing village funds. This law regulates the governance, planning, implementation, and accountability of using village funds to ensure that allocating funds provides maximum benefits for village communities. This study aims to outline and evaluate the Good Corporate Governance principles used by the Jambanan Village Government in the Sidoharjo District of the Sragen Regency in managing village money. This kind of study combines a qualitative and descriptive methodology. Based on real-world occurrences, this study design is thought to be the best way to thoroughly describe the good governance concepts in the Jambanan Village administration. The methods used for gathering data include observation, documentation, and interviews. The selected informants are the village head, village secretary, village treasurer, community leaders, neighborhood association, youth organization leader, and village deliberation body. The study's findings show that the values of independence, responsibility, accountability, and fairness have all been appropriately applied. As a result, the transparency concept has not been correctly applied. The outcome showed that Jambanan village governance's money management practices did not adequately apply the concepts of good corporate governance.